The market for government bonds - Park, Andreas (Henry Stewart Talks, 2009)
The trading of government bonds in secondary markets, The importance of market trading mechanisms, Possible organizational forms of trading and their impact on market liquidity, execution costs, and price volatility, Current market structures and stylized features of government securities trading